2005
DOI: 10.1016/j.nlm.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Memory enhancement by a semantically unrelated emotional arousal source induced after learning

Abstract: It has been well established that moderate physiological or emotional arousal modulates memory. However, there is some controversy about whether the NOT THE PUBLISHED VERSION; this is the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation at the bottom of the page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 53 publications
6
59
3
Order By: Relevance
“…As such, it is impossible to decipher in these studies whether the effect is on attention, encoding, consolidation or some combination of these phases. However, several recent studies have demonstrated memory modulatory effects in human participants by comparable mechanisms of action as have been shown in rodent studies using various posttraining treatments including norepinephrine (Southwick et al, 2002), glucose (Manning, Parsons, & Gold, 1992), nicotine (Colrain, Mangan, Pellett, & Bates, 1992), and non-invasive treatments such as muscle tension (Nielson & Jensen, 1994;Nielson, Radtke, & Jensen, 1996), stress (Cahill, Gorski, & Le, 2003) and negative and positive emotional arousal (Nielson & Bryant, 2005;Nielson, Yee, & Erickson, 2005). Importantly, no human study has yet examined the time-dependency of these effects; no study has varied the delay of the intervention after learning.…”
Section: Introductionmentioning
confidence: 78%
“…As such, it is impossible to decipher in these studies whether the effect is on attention, encoding, consolidation or some combination of these phases. However, several recent studies have demonstrated memory modulatory effects in human participants by comparable mechanisms of action as have been shown in rodent studies using various posttraining treatments including norepinephrine (Southwick et al, 2002), glucose (Manning, Parsons, & Gold, 1992), nicotine (Colrain, Mangan, Pellett, & Bates, 1992), and non-invasive treatments such as muscle tension (Nielson & Jensen, 1994;Nielson, Radtke, & Jensen, 1996), stress (Cahill, Gorski, & Le, 2003) and negative and positive emotional arousal (Nielson & Bryant, 2005;Nielson, Yee, & Erickson, 2005). Importantly, no human study has yet examined the time-dependency of these effects; no study has varied the delay of the intervention after learning.…”
Section: Introductionmentioning
confidence: 78%
“…This interaction between encoding and postencoding arousal may help explain the lack of post-training arousal enhancement obtained in the present study. In humans, although post-encoding arousal can enhance memory for prior presentations of nonarousing events (Nielson et al 2005;Anderson et al 2006), this enhancement has been shown to be most prominent for more arousing events (Cahill and Alkire 2003;. For example, it has been shown that posttraining administration of either epinephrine (Cahill and Alkire 2003) or cold pressor stress ) enhances longterm memory (1 wk) for arousing material encountered during the training episode but not for nonarousing material.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that negative effects of stress may be confined to disrupting information that has already been encoded. However, some studies suggest that stress can impair learning and that memory can be enhanced by stress (Nielson et al 2005). Many of these reports, interestingly enough, involve differences that arise either because of gender or because of age.…”
Section: Differences Sex Differences In Stress Effects On Learningmentioning
confidence: 99%